Comparison of norepinephrine and phenylephrine boluses during spinal anesthesia for cesarean delivery - Chandraleela Sundararajan; Chinthavali Sujatha; Arthi Asokan (Asian Journal of Medical Sciences, 2022)
Background: Cesarean sections are frequently carried out under spinal anesthesia (SA) to reduce the risk of neonatal drug transfer and airway difficulties associated with general anesthesia. Maternal hypotension is a typical consequence following SA, despite sufficient fluid loading. Aims and Objectives: The aim of this study was to evaluate the efficacy of norepinephrine and phenylephrine in treating spinal hypotension caused by cesarean delivery. Materials and Methods: This hospital-based interventional study was carried out at Sri Venkateswaraa Medical College Hospital and Research Centre, Ariyur, Puducherry from February 2020 to March 2022. Eighty patients were included in our trial and were split equally into two groups at random following approval by an ethical committee and written informed consent. Age, weight, height, and American Society of Anesthesiologists physical state of the patients was equivalent across the two groups. Results: In our study, mean age found in N group (25.96±2.046) and P group (24.84±1.748) which were insignificant. Vasopressor bolus dose needed for the treatment of hypotension was considerably less in Group N patients (1.71±0.77 vs. 2.43±1.01, P=0.024). Group P had a higher incidence of bradycardia, although the difference was statistically insignificant (four patients vs. eight patients P=0.242). The fetal parameters such as birth weight, umbilical PH, PCO, PO2, and Apgar 1 and 5 min were comparable across the two groups, and no statistically significant differences were found. Conclusion: Intermittent norepinephrine boluses are a successful treatment for spinal hypotension during cesarean delivery. We found no evidence that norepinephrine had a detrimental effect on the newborn outcome as compared to phenylephrine, when used to maintain blood pressure during spinal and combined spinalepidural anesthesia for cesarean birth.